Hirschsprung disease and other intestinal neuropathies in children - Zdanowicz, Katarzyna; Reszeć, Joanna; Dzienis-Koronkiewicz, Ewa; Hermanowicz, Adam; Lebensztejn, Dariusz (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Proper intestinal motility depends on interaction between muscles, nerve cells, and tendinous connective tissue of muscularis propria. Intestinal motility disorders refer to varied intestinal neuromuscular pathologies, including enteric neuropathies. The most common symptoms of these diseases are delayed passage of meconium in newborns and chronic constipation in infants and older children. If organic causes of clinical features are detected, a further multidisciplinary team approach for the management of these patients is recommended. Entities discussed in this review include Hirschsprung disease, hypoganglionosis, intestinal neuronal dysplasia, ganglioneuromatosis, and chronic intestinal pseudo-obstruction. Emphasis is given to the clinical symptoms and diagnostic features that distinguish these conditions enabling faster diagnosis and appropriate treatment.